Protocol for process evaluation of a randomised controlled trial of family-led rehabilitation post stroke (ATTEND) in India. Issue 9 (15th September 2016) - Liu, Hueiming; Lindley, Richard; Alim, Mohammed; Felix, Cynthia; Gandhi, Dorcas B C; Verma, Shweta J; Tugnawat, Deepak Kumar; Syrigapu, Anuradha; Ramamurthy, Ramaprabhu Krishnappa; Pandian, Jeyaraj D; Walker, Marion; Forster, Anne; et al.
Abstract : Introduction: We are undertaking a randomised controlled trial (fAmily led rehabiliTaTion aftEr stroke in INDia, ATTEND) evaluating training a family carer to enable maximal rehabilitation of patients with stroke-related disability; as a potentially affordable, culturally acceptable and effective intervention for use in India. A process evaluation is needed to understand how and why this complex intervention may be effective, and to capture important barriers and facilitators to its implementation. We describe the protocol for our process evaluation to encourage the development of in-process evaluation methodology and transparency in reporting. Methods and analysis: The realist and RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance) frameworks informed the design. Mixed methods include semistructured interviews with health providers, patients and their carers, analysis of quantitative process data describing fidelity and dose of intervention, observations of trial set up and implementation, and the analysis of the cost data from the patients and their families perspective and programme budgets. These qualitative and quantitative data will be analysed iteratively prior to knowing the quantitative outcomes of the trial, and then triangulated with the results from the primary outcome evaluation. Ethics and dissemination: The process evaluation has received ethical approval for all sites in India. In low-income and middle-income countries, the available human capital can form an approach to reducing the evidence practice gap, compared with the high cost alternatives available in established market economies. This process evaluation will provide insights into how such a programme can be implemented in practice and brought to scale. Through local stakeholder engagement and dissemination of findings globally we hope to build on patient-centred, cost-effective and sustainable models of stroke rehabilitation. Trial registration number: CTRI/2013/04/003557.